Blood transfusion versus hydroxyurea in beta-thalassemia in Iran: a cost-effectiveness study. Issue 7 (9th August 2018) - Ravangard, Ramin; Mirzaei, Zahra; Keshavarz, Khosro; Haghpanah, Sezaneh; Karimi, Mehran
ABSTRACT: Introduction : Thalassemia intermedia is a type of anemia which has several treatments modalities. We aimed to study the cost effectiveness of two treatments, including blood transfusion and hydroxyurea, in patients with beta-thalassemia intermedia in south of Iran referred to a referral center affiliated to Iran, Shiraz University of Medical Sciences in 2015. Materials and methods : This was a cost-effectiveness study which was conducted on 122 patients with beta-thalassemia intermedia. The indicator of effectiveness in this study was the reduction of growth disorder (normal BMI). Data analysis was done using SPSS 21, Excel 2010 and Treeage 2011. Finally, the one-way sensitivity analysis was performed to determine the robustness of the results. Results : The average annual costs of blood transfusion and the use of hydroxyurea in 2015 were 20733.27 purchasing power parity (PPP) and 7040.29 PPP, respectively. The effectiveness of blood transfusion was57.4% while in hydroxyurea group was 60.7%. Conclusion : The results showed that the cost effectiveness of using hydroxyurea was more than that of blood transfusion. Therefore, it is recommended that the use of hydroxyurea in the treatment of patients with beta-thalassemia intermedia would become the first priority, and more basic and supplementary insurance coverage for treating such patients using hydroxyurea should be considered.